Quaternionic Hardy spaces in the open unit ball and half space and Blaschke products. (March 2015) - Alpay, Daniel; Colombo, Fabrizio; Sabadini, Irene
Abstract: The Hardy spaces H 2 (B) and H 2 (H+ ), where B and H+ denote, respectively, the open unit ball of the quaternions and the half space of quaternions with positive real part, as well as Blaschke products, have been intensively studied in a series of papers where they are used as a tool to prove other results in Schur analysis. This paper gives an overview on the topic, collecting the various results available.